Applied mechanics and manufacturing technology : selected, peer reviewed papers of the 2011 International Conference on Applied Mechanics and Manufacturing Technology (AMMT 2011), August 4-7, 2011, Bali, Indonesia - Gaol, Ford Lumban (Applied mechanics and materials, 2011)
These proceedings of the 2011 International Conference on Applied Mechanics and Manufacturing Technology (AMMT'11) focused on applied mechanics and its application to manufacturing technology, and thus provided a forum within which researchers and practitioners could exchange research results and share developmental experiences in these fields. The contents represent a timely survey of the subjects covered. Review from Book News Inc.: The 46 papers selected for the August 2011 conference test the properties of nickel titanium orthodontic wires, metallic glass particle reinforced aluminum matri.